The effect of a self-constructed material on children's physical activity during recess - Antonio Méndez-Giménez; José-Antonio Cecchini; Javier Fernández-Río
ABSTRACT OBJECTIVE To analyze whether an intervention supported by free play with a self-constructed material increases the level of physical activity of students during recess. METHODS The participants were 166 children of third to sixth grade, between nine and 12 years old (average = 10.64; SS = 1.13). An experimental project was conducted with pre-test and post-test measurement, and a control group. Experimental group participants built cardboard paddles (third and fourth) and flying rings (fifth and sixth), a material they used freely for one week during recess. ActiGraph-GT3X accelerometers were used to measure physical activity. An ANOVA of repeated measures was used to find differences between groups and genders. RESULTS Significant intervention effects were found in the analyzed variables: sedentary activity (F = 38.19; p < 0.01), light (F = 76.56; p < 0.01), moderate (F = 27.44; p < 0.01), vigorous (F = 61.55; p < 0.01), and moderate and vigorous (F = 68.76; p < 0.01). Significant gender differences were shown (time × group × gender) for moderate (F = 6.58; p < 0.05) and vigorous (F = 5.51; p < 0.05) activity. CONCLUSIONS The self-constructed material is effective to increase the physical activity levels of children during recess; it decreases sedentary activity and light physical activity and increases the time devoted to moderate physical activity and vigorous physical activity, both in boys and in girls. The boys had an increase in vigorous physical activity and the girls in moderate physical activity. Due to its low cost, this strategy is recommended for administrators and teachers to increase the physical activity of children during recess.